Conceptual Study of Applications of Prakruthi Sama Samavetha and Vikruthi Visama Samavetha Siddhanta (International Journal of Ayurveda and Pharma Research, 2024)
Ayurveda is a holistic science that works for a healthy, wealthy and happy life. The wisdom of Ayurveda is based on various theories and principles. To know the science properly one should have the thorough knowledge of all the fundaments. The concept of Prakruthi Sama Samvetha Siddhanta and Vikriti Visama Samavetha Siddhanta is one such basic principle of Ayurveda. Prakruthi sama Samavetha Siddhanta and Vikriti Visama Samavetha Siddhanta are the given by Acharya charaka. While describing the relation between Rasa - Dravya and Dosa-Vyadhi. These two Siddanthans helps in understanding the concept of diagnosis, treatment. Dravya is the entity which has been given with prime importance for its role in prevention and treatment of different ailments. Generally Dravyas acts according to Rasa, Guna, Virya, and Vipaka. In some other conditions the action of Dravya cannot be expressed with the help of Rasa, Guna, Virya, Vipaka. This study is carried out with a view to know the applicability of Prakruthi Sama Samvetha Siddhanta and Vikriti Visama Samavetha Siddhanta in diagnosis and treatment purpose.